Immune microenvironment of Epstein-Barr virus (EBV)-negative compared to EBV-associated gastric cancers: implications for immunotherapy - Ke Xu; Qingfeng Zhu; Suzanne L Topalian; Robert A Anders; Janis M Taube; Mark Yarchoan; Keziban Ünsal-Kaçmaz; Logan L Engle; Tracee L McMiller; Sepideh Besharati; Junghwa Lee; Feriyl Bhaijee; et al. (Journal for ImmunoTherapy of Cancer)
Background Gastric carcinomas (GC) are aggressive malignancies, and only ~15% of patients respond to anti-programmed cell death (ligand) 1 (PD-(L)1) monotherapy. However, Epstein-Barr virus (EBV)-associated GCs (~5–10% of GCs) often harbor PD-L1 and PD-L2 chromosomal amplifications and robust CD8+ T cell infiltrates, and respond at a high rate to anti-PD-1. The current study compares the tumor immune microenvironments (TiMEs) of EBV+ versus EBV(−) GCs.Methods Over 1000 cases of primary invasive GCs were screened to identify 25 treatment-naïve specimens for study (11 EBV+, 14 EBV(−)). Quantitative immunohistochemistry (IHC) was conducted for markers of immune cell subsets and co-regulatory molecules. Gene expression profiling (GEP) was performed on RNAs isolated from macrodissected areas of CD3+ T cell infiltrates abutting PD-L1+ stromal/tumor cells, using multiplex quantitative reverse transcriptase PCR for a panel of 122 candidate immune-related genes.Results IHC revealed that 17/25 GCs contained PD-L1+ stromal cells, with no significant difference between EBV+/- specimens; however, only 3/25 specimens (all EBV+) contained PD-L1+ tumor cells. CD8+ T cell densities were higher in EBV+ versus EBV(−) tumors (p=0.044). With GEP normalized to the pan-leukocyte marker PTPRC/CD45, EBV+ GCs overexpressed ITGAE (CD103, marking intraepithelial T cells and a dendritic cell subset) and the interferon-inducible genes CXCL9 and IDO1. In contrast, EBV(−) tumors overexpressed several functionally-related gene groups associated with myeloid cells (CD163, IL1A, NOS2, RIGI), immunosuppressive cytokines/chemokines (CXCL2, CXCR4, IL10, IL32), coinhibitory molecules (HAVCR2/TIM-3 and VSIR/VISTA), and adenosine pathway components (ENTPD1/ CD39 and NT5E/CD73). Notably, compared with EBV+ GCs, EBV(−) GCs also overexpressed components of the cyclooxygenase 2 (COX-2)/prostaglandin E2 (PGE2) pathway associated with cancer-promoting inflammation, including PTGS2/COX-2 (most highly upregulated gene, 32-fold, p=0.005); prostaglandin receptors PTGER1 (EP1; up 21-fold, p=0.015) and PTGER4 (EP4; up twofold, p=0.022); and the major COX-2-inducing cytokine IL1B (up 11-fold, p=0.019). Consistent with these findings, COX-2 protein expression trended higher in EBV(−) versus EBV+ GCs (p=0.068).Conclusions While certain markers of immunosuppression are found in the GC TiME regardless of EBV status, EBV(−) GCs, which are much more common than EBV+ GCs, overexpress components of the COX-2/PGE2 pathway. These findings provide novel insights into the immune microenvironments of EBV+ and EBV(−) GC, and offer potential targets to overcome resistance to anti-PD-(L)1 therapies.